"One country, two systems" after the Umbrella movement: problems and prospects. Issue 4 (2nd October 2017) - Cheung, Chor-yung
Abstract : Purpose: The purpose of this paper is to assess critically the political challenges facing Hong Kong's "one country, two systems" policy following the Umbrella Movement and to evaluate the territory's democratic and autonomous future. Design/methodology/approach: A critical, contextual, and analytical approach has been adopted to evaluate the problems and prospects for post-Umbrella Movement Hong Kong. Findings: The contradictions embedded in the "one country, two systems" policy have become apparent since the Umbrella Movement arose and Hong Kong's political and democratic future is as problematic as its prospects are uncertain, though the possibility of some rapprochement between Hong Kong and Beijing should not be ruled out completely. Research limitations/implications: The critical evaluation offered by this paper is no scientific prediction. Social scientific analysis of this kind is suggestive rather than definitive. The informed discussion offered by this paper will help readers to better understand the strengths and weaknesses inherent in Beijing's "one country, two systems" policy and the tortuous process of democratization in Hong Kong. The conclusion drawn in the paper points to a possible way out of the political impasse that is facing post-Umbrella Movement Hong Kong. Originality/value: This paper is a pioneering study of the most important political conflict between Beijing and Hong Kong since 1997, the conclusion of which may have important political and policy implications for both China and Hong Kong.